2006
DOI: 10.1002/art.21642
|View full text |Cite
|
Sign up to set email alerts
|

Association of the IL1 gene cluster with susceptibility to ankylosing spondylitis: An analysis of three Canadian populations

Abstract: Objective. To examine the association between the IL1 gene cluster and susceptibility to ankylosing spondylitis (AS) in 3 independent case-control cohorts.Methods. We analyzed 394 patients and 446 controls from Alberta, Newfoundland, and Toronto, Canada. Samples were genotyped using a panel of 38 single-nucleotide polymorphism (SNP) markers within the IL1 gene cluster. Data from 20 informative and nonredundant SNP markers were analyzed using several association test strategies. First, we used the program WHAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 65 publications
(61 reference statements)
1
46
0
5
Order By: Relevance
“…It is highly associated with HLA-B27, but analyses of recurrence risk among family members suggest that at least 3 other genetic loci in addition to HLA-B27 are required to confer full susceptibility to AS (2). Despite several large genome-wide linkage studies of AS families (3)(4)(5)(6), the IL1 locus is the only significant non-major histocompatibility complex (non-MHC) susceptibility locus that has thus far emerged (7,8). However, 2 family-based association studies, 1 of which examined 244 affected sibpairs, showed no evidence of linkage to genes in the IL1 cluster (9,10).…”
Section: Conclusion Our Results Indicate That the Tnap Haplotype Rs3mentioning
confidence: 99%
“…It is highly associated with HLA-B27, but analyses of recurrence risk among family members suggest that at least 3 other genetic loci in addition to HLA-B27 are required to confer full susceptibility to AS (2). Despite several large genome-wide linkage studies of AS families (3)(4)(5)(6), the IL1 locus is the only significant non-major histocompatibility complex (non-MHC) susceptibility locus that has thus far emerged (7,8). However, 2 family-based association studies, 1 of which examined 244 affected sibpairs, showed no evidence of linkage to genes in the IL1 cluster (9,10).…”
Section: Conclusion Our Results Indicate That the Tnap Haplotype Rs3mentioning
confidence: 99%
“…A significant difference of the distribution of haplotypes was found between the AS affected and healthy individuals. On the contrary, in earlier studies no association between AS and IL1-F3 gene was found Jin, et al, 2004;Kim, et al, 2005;Maksymowych, W. P., et al, 2006;Timms, A. E., et al, 2004). These findings were also observed in the genome scan carried out by North American Spondylitis Consortium (NASC) (Jin, et al, 2004).…”
Section: Il1 Gene Clustermentioning
confidence: 88%
“…In nine IL-1 genes, were identified SNPs showing significant association with AS (Timms, A. E., et al, 2004). Maksymowych et al identified 14 SNPs with high association in at least one cohort (Maksymowych, W. P., et al, 2006). The most significant cohorts were in IL1-F1 and IL1-F2.…”
Section: Il1 Gene Clustermentioning
confidence: 99%
“…According to the inclusion criteria, 13 studies (McGarry et al, 2001;van der Paardt et al, 2002;Maksymowych et al, 2003;Timms et al, 2004;Kim et al, 2005;Chou et al, 2006;Lin et al, 2006;Maksymowych et al, 2006;Yang et al, 2007;Agrawal et al, 2008;Liu et al, 2008;Sims et al, 2008;Guo et al, 2010) were included and 53 were excluded. A flow chart of the study selection process is shown in Figure 1.…”
Section: The Characteristics Of Included Studiesmentioning
confidence: 99%